Influence of vehicles on antioxidant efficacy in hair. Issue 19 (8th February 2016) - Rubio, L.; Alonso, C.; Martí, M.; Martínez, V.; Coderch, L.
Abstract : Microspheres are the best vehicle to increase the antioxidant efficacy of gallic acid in hair. Abstract : The UV radiation of sunlight is known to damage human hair, causing fibre degradation. Gallic acid (GA) was used as an active principle because of its antioxidant properties, which confer protection against free radicals. Encapsulation technologies, such as polymer-based (micro- and nano-spheres, capsules) and lipid-based systems (liposomes, emulsions), have been used to enhance and prolong the effectiveness of active ingredients. In this study, GA loaded in PCL microspheres (GA-Micro) and GA encapsulated in PC liposomes (GA-Lipo) were prepared to study their effectiveness as antioxidants when applied to human hair compared with treatment with free GA. The antioxidant effects of these structures were measured by the Bradford colorimetric assay and the thiobarbituric acid (TBA) assay and fluorescence spectroscopy using 2, 7-dichlorodihydrofluorescein (DCFH) as the fluorescent probe. The penetration of GA into hair depending on the vehicle was also evaluated. Higher penetration of GA was found in hair fibres treated with GA encapsulated vehicles. The results of the antioxidant studies showed that the efficacy of GA increased when it was encapsulated in liposomes and microspheres, as well as when the studies were performed immediately after antioxidant treatment. Moreover, GA that was loaded into microspheres retained its antioxidant efficacy for one and two months after treatment, indicating that the microspheres could preserve the antioxidant effect of GA. Moreover, the spectrofluorometric method was found to be the best method to evaluate the efficacy of GA embedded in different vehicles.